The Economic and Fiscal Consequences of Financial Crises - Reinhart, Carmen M. (World Bank, 2012)
The Ds: Sharp economic downturns follow banking crises; with government revenues falling, fiscal deficits worsen; deficits lead to debt; as debts pile up rating downgrades follow. For the most fortunate countries it does not end in default.